2018
DOI: 10.1186/s12986-018-0252-4
|View full text |Cite
|
Sign up to set email alerts
|

Dietary canolol protects the heart against the deleterious effects induced by the association of rapeseed oil, vitamin E and coenzyme Q10 in the context of a high-fat diet

Abstract: BackgroundObesity progressively leads to cardiac failure. Omega-3 polyunsaturated fatty acids (PUFA) have been shown to have cardio-protective effects in numerous pathological situations. It is not known whether rapeseed oil, which contains α-linolenic acid (ALA), has a similar protective effect. Omega-3 PUFAs are sensitive to attack by reactive oxygen species (ROS), and lipid peroxidation products could damage cardiac cells. We thus tested whether dietary refined rapeseed oil (RSO) associated with or without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 45 publications
3
14
0
Order By: Relevance
“…Similarly to palm oil-rich diet, the diet rich in lard also effected in an increase of AA in the heart membrane [91]. The authors suggest that AA has a strong effect on vessel dilatation and its accumulation may promote coronary flow, which can result in an increased mechanical function of the heart [90].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarly to palm oil-rich diet, the diet rich in lard also effected in an increase of AA in the heart membrane [91]. The authors suggest that AA has a strong effect on vessel dilatation and its accumulation may promote coronary flow, which can result in an increased mechanical function of the heart [90].…”
Section: Discussionmentioning
confidence: 97%
“…Only few publications indicate that TBARS level does not change or decreases in the cardiac tissue in diabetic rodents [61,89]. The lowered TBARS level in the heart was observed by the authors, who fed the rats with high-fat diet (with 30% of fat from palm oil) for 11 weeks [90]. These authors explain the result by changes in polyunsaturated fatty acids (PUFA) profile in phospholipids of the heart membrane-there was a significant increase in arachidonic acid (AA) in the heart membrane of rats on palm oil-rich diet, compared to the membrane of rats fed with standard chow [90].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the protein carbonyl content in heart tissue did not differ between SD and HFD mice. Moreover, Leger et al [85] found that HFD led to decrease of cardiac oxidative stress and apoptosis rate in rats. This was associated with increased arachidonic acid proportion in membrane phospholipids.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary EPA is protective during sepsis, but we do not know whether other n-3 PUFAs such as α-linolenic (C18:3 n-3 or ALA) acid is efficient. Indeed, in contrast with dietary EPA, ALA does not allow the easy accumulation of EPA in membrane phospholipids [20]. Phospholipid EPA is directly accessible to the cyclooxygenase enzyme via the action of phospholipase A2.…”
Section: Introductionmentioning
confidence: 99%